Sistemas de identificação modulares em documentos do Detran : uma forma alternativa de relacionar matemática e trânsito - Barbosa, Jhonattan Pinto (2015)
This dissertation has the main aim, be a facilitator instrument on the task to relate the math with the transit theme. For this, we will use the Modular Arithmetic concepts existing on the Modular Identi cation Systems that were applied to guides and documents from Detran/MT, because we understand that the pupil when come into the nal series from the elementary school and consequently high school already has the necessary instruments to the comprehension of such concepts due to their elemental nature and applicability to student's everyday. However, before we approach this subject we presented some preliminaries concepts, that sustain the utilized results. Furthermore, on the last chapter we present one activity that can be applied on nal series from the elementary school and on the high school too, with the intuit to demonstrat the real possibility to approach the tra c theme on the math classes, without the necessity to use the tables, graphics or data about tra c acidentes, numbers from the vehicle eet, or other statistical indicators.